2018
DOI: 10.1186/s12915-018-0618-0
|View full text |Cite
|
Sign up to set email alerts
|

Biological clock function is linked to proactive and reactive personality types

Abstract: BackgroundMany physiological processes in our body are controlled by the biological clock and show circadian rhythmicity. It is generally accepted that a robust rhythm is a prerequisite for optimal functioning and that a lack of rhythmicity can contribute to the pathogenesis of various diseases. Here, we tested in a heterogeneous laboratory zebrafish population whether and how variation in the rhythmicity of the biological clock is associated with the coping styles of individual animals, as assessed in a behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 52 publications
2
49
0
Order By: Relevance
“…These findings again suggested the evolution of a foraging-optimizing timing of activity, likely linked to boldness. Our finding are supported by a recent study demonstrating that proactive zebrafish (i.e., risk-taking individuals) are more active in the first hours of photophase compared to reactive ones (29). Relatedly, the self-feeding activity events of the small-harvested line extended to the hours before and after light-on.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…These findings again suggested the evolution of a foraging-optimizing timing of activity, likely linked to boldness. Our finding are supported by a recent study demonstrating that proactive zebrafish (i.e., risk-taking individuals) are more active in the first hours of photophase compared to reactive ones (29). Relatedly, the self-feeding activity events of the small-harvested line extended to the hours before and after light-on.…”
Section: Discussionsupporting
confidence: 89%
“…Recent studies on zebrafish demonstrated that proactive and reactive phenotypes in zebrafish explain a large fraction of the variation of the brain transcriptome including expression of genes related to the circadian system (28). Moreover, proactive phenotypes were found to have more robust molecular (i.e., clock genes daily expression), humoral (i.e., daily secretion of melatonin) and behavioral (i.e., locomotor activity) oscillations of the circadian system (29). However, both of the cited studies measured transcripts abundance under LD conditions; therefore the truly endogenous nature of the circadian molecular clockwork could have been masked by the LD cycle.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations